Visual perception games for autistic learners: Design & development - Mohd C.K.N.C.K.; Shahbodin F.; Azni A.H.; Jano Z. (Association for Computing Machinery, 2024)
The use of information communication technologies (ICTs) in therapy offers new perspectives for treating many domains in individuals with autism spectrum disorders (ASD) because it is used in many different ways and settings and they are attractive to the patients. Students with autism have a high incidence of visual perception problems. They often have difficulty recognizing, remembering, organizing and interpreting visual images. As a result, they are easily confused in situations where written or pictorial symbols are utilised for learning. The paper reported the design and development of autism diagnostic tool using serious games technique. It is a tool for special education teachers to diagnose visual perception problems among autistic students. The game is known as Vi-Per Games. A diagnostic tool known as Vi-Per Games has been developed based on ADDIE model. Vi-Per Games is able to diagnose autistic students without the needs for teachers to have some experience and knowledge of diagnosing visual perception. This prototype will be a high-tech solution to diagnose visual perception problems designed for autistic children. 2019 Association for Computing Machinery.